Assessing dietary pattern and its association with hypertension among the elderly in the Tano North District in the Brong Ahafo Region, Ghana - Gyamea, Helina (2018)
A thesis submitted to the Department of Biochemistry and Biotechnology, College of Science, in partial fulfillment of requirement for the Degree of Master of Science in Nutrition and Dietetics.